Migration and political elite formation. (c2018) - Maalouf, Wahib (2018)
Migration has been impacting political elite formation in Lebanon since the 1930s, yet its role in that matter remained understudied. The main reason behind this is the relative prevalence in elite studies of “methodological nationalism”, which, in one of its variants, “confines the study of social processes to the political and geographic boundaries of a particular nation-state”. As such, these studies fail to account for “cross-border” activities which have an impact on political processes in the country of origin. Hence, this study has a twofold objective. First, it aims to fill a gap in the scholarly migration literature by conceptualizing the role played by migration in political elite formation in the countries of origin. Second, it seeks to provide an indepth analysis of the impact of migration on the formation and transformation of Lebanon's political elite in the postwar period (1990-2018). I focus on the postwar period as one which has witnessed an increasingly important role for Lebanese return migrants on the domestic political scene. This study argues that adopting a “transnational lens” that captures “cross-border” activities reveals a significant role for migrant economic capital in the processes of acquiring elite status in Lebanon by the respective migrants. The study invokes sociologist Pierre Bourdieu’s notions of “capital” and “convertibility of capital”, and argues that extending the Bourdieusian framework beyond the contours of the nation-state allows us to understand how one (or more) form of migrant capital could later be converted into political capital (and hence elite status) in Lebanon.